2015
DOI: 10.1523/jneurosci.3572-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Identity Information Extraction from Noisy Face Images

Abstract: Previous research has made significant progress in identifying the neural basis of the remarkably efficient and seemingly effortless face perception in humans. However, the neural processes that enable the extraction of facial information under challenging conditions when face images are noisy and deteriorated remains poorly understood. Here we investigated the neural processes underlying the extraction of identity information from noisy face images using fMRI. For each participant, we measured (1) face-identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 88 publications
0
15
2
Order By: Relevance
“…Rodent models demonstrate that PME alters striatal gene expression of the DA D2 receptor (D2R) (DiNieri et al, 2011 ). Taken together with the reportedly high striatal CB1R concentration (Glass et al, 1977 ; Herkenham et al, 1991 ; Hermann et al, 2015 ), D2R–CB1R interactions (Anderson et al, 1996 ) following repeated THC exposure are likely to disrupt developing motor control circuits and may contribute to the current finding of reduced functional connectivity between caudate and cerebellar regions. Both structures play important roles in integrating and coordinating motor and non-motor activity, language, memory, and learning.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Rodent models demonstrate that PME alters striatal gene expression of the DA D2 receptor (D2R) (DiNieri et al, 2011 ). Taken together with the reportedly high striatal CB1R concentration (Glass et al, 1977 ; Herkenham et al, 1991 ; Hermann et al, 2015 ), D2R–CB1R interactions (Anderson et al, 1996 ) following repeated THC exposure are likely to disrupt developing motor control circuits and may contribute to the current finding of reduced functional connectivity between caudate and cerebellar regions. Both structures play important roles in integrating and coordinating motor and non-motor activity, language, memory, and learning.…”
Section: Discussionmentioning
confidence: 69%
“…Fusiform gyrus has been related to recognition of faces, words, and emotional content in facial expressions. Right fusiform activation, specifically, is linked to determining whether a “face-like” image is truly a face (Massachusetts Institute of Technology, 2012 ), and to discrimination of facial identity within a complex visual presentation (Hermann et al, 2015 ). Reduced local resting state connectivity within the right fusiform is reported in adults with autism spectrum disorder (Itahashi et al, 2015 ), a disease characterized by impaired perception of facial social cues.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of FFA and/or OFA has been related to the detection, recognition, or discrimination of faces (Grill-Spector et al 2000;GrillSpector et al 2004;Hermann et al 2015;Nestor et al 2008). Huang et al (2014) measured face recognition in an old/new paradigm and found that the participants' recognition ability correlated with the face selectivity of the FFA and OFA, measured by estimating the differential response of the areas for face and non-face object stimuli.…”
Section: Network Specific Fmriamentioning
confidence: 99%
“…Fourth, several studies on face recognition in ASD have also found not only supramodal brain regions impaired, but a processing impairment in the fusiform face area (FFA; e.g. Schultz et al , 2000; Pierce et al , 2001; Domes et al , 2013), a brain region that is associated with face perception and identity processing (Eger et al , 2004; von Kriegstein et al , 2008; Hermann et al , 2015; for review see Bernstein and Yovel, 2015). We therefore speculate that a dysfunctional precuneus is not the primary cause for the person recognition deficits for voices and faces in ASD.…”
Section: Discussionmentioning
confidence: 99%